Analysis of occupational health and safety at skin cracker factory using Hazard and Operability Study (HAZOP) - Santika Sari; Hashifah Husna; Laela Aziani Novitasari; Alfika Putri Kirana; Muhammad Sirozjudin Munir; Adinda Zahara Lailah Zain; Tariska Aaliyah Tsabitah (Universitas Sultan Ageng Tirtayasa, 2022)
The Mubarok Skin Cracker Factory is a home industry that produces skin crackers from cowhide, raw, and cooked crackers. Based on the interviews with factory owners, there have been several work accidents, and the production room has very minimal lighting and air ventilation. Based on these problems, the method used is the Hazard and Operability Study (HAZOP), which aims to identify sources of hazards and potential work accidents in the production process to prevent work accidents. The risk matrix analysis shows as much as 24% of the risk is classified as extreme, 65% is classified as high risk, and 12% is classified as moderate risk. In addition, 17 sources of danger were found, namely knives, slippery floors, smoke, hot water, drying roofs, fire, smoke, hot water, ash flakes, hot tanks, wooden board, chopper, loads carried by workers, ovens, hot oil, hot frying pan, hanging boards, and cramped workplaces. The recommendations given by the researcher are to apply health and safety environment regulations and use PPE (Personal Protective Equipment) for employees while working, replace damaged equipment, and implement health promotion in factories.